The influence of integrated governance, and creating shared value on sustainability performance, with organizational culture as moderation - Rusgowanto, Fransisca Hanita; Murwaningsari, Etty; Augustine, Yvonne; San, Ong Tze Tze (World Scientific and Engineering Academy and Society, 2025)
Purpose-The objectives of this research is to analyze the influence of integrated corporate governance (ICG) on sustainability performance and creating shared value on sustainability performance by moderating organizational culture. This research is conducted to evaluate the impact of integrated corporate governance (ICG) on sustainability achievement as well as the role of shared value creation in influencing sustainability performance by considering the moderation of corporate culture. Design/methodology/approach – The participants of this study consist of companies listed on IDX except banking companies. Quantitative research methods using primary data. Data processing uses partial least square (PLS) software and moderated regression analysis. Findings-The results showed that integrated corporate governance on sustainability performance did not strengthen the moderator organizational culture relationship, while creating shared value on sustainability performance had a strong relationship with moderated organizational culture. The CSV variable, which is the novelty of this research, emphasizes the explanation of purpose, passion, and partnership in the company's organizational culture, which is directly related to sustainability performance. Originality/value-This research develops a further measurement of CSV by adding the dimensions of purpose, passion, and partnership. Emphasizing the moderating role of organizational culture in catalyzing the relationship between CSV and sustainability performance. The practical implications resulting from this research highlights the importance of implementing integrated governance and CSV strategies to improve corporate competitiveness while having a beneficial influence on communities and the environment.